Sclerosed hemangioma of the liver: Concordance of MRI features with histologic characteristics. Issue 4 (7th November 2013) - Ridge, Carole A.; Shia, Jinru; Gerst, Scott R.; Do, Richard K.G.
Abstract : Purpose: To correlate the MRI features of sclerosed hemangiomas with histologic appearance. Materials and Methods: A medical record search identified patients with sclerosed hemangioma who underwent MRI and biopsy/resection from January 2000 to March 2012 for this retrospective institutional review board approved study. Two radiologists independently performed image analysis. A pathologist evaluated lesion histologic characteristics. Results: Twelve patients (median age 65; range 41–78 years) were included; 7/12 patients had typical hemangiomas which were also analyzed. Sclerosed hemangiomas were less often moderately T2 hyperintense (5/11 45%; compared with 7/7, 100%; P = 0.0377) and demonstrated moderate arterial phase enhancement less frequently (4/12, 33% compared with 7/7, 100%; P = 0.0128) than typical hemangiomas. Markedly sclerosed hemangiomas (N = 7) exhibited the least "typical" findings, including mild T2 hyperintensity (5/7; 71%), absent arterial phase enhancement (4/7; 57%), mild portal venous phase enhancement (6/7; 86%), and absent centripetal fill‐in (6/7; 86%). Arterial phase hyperenhancement occurred more often in mild/moderately sclerosed hemangiomas (3/5; 60%) compared with markedly sclerosed hemangiomas (1/7; 14%). Conclusion: Sclerosed hemangiomas exhibit MRI features that appear to correspond with the degree of sclerosis. These features coupled with the presence of other typical hemangiomas may aid in prospectively diagnosing sclerosed hemangioma.J. Magn. Reson. Imaging 2014;39:812–818. ©2013 Wiley Periodicals, Inc.